The Influence of Management, Personnel Performance, and Organizational Culture on the Quality of the Ordnance School - Waskito, Haris (Dinasti International Journal of Management Science, 2025)
This research aims to determine the influence of management, personnel performance, and organizational culture and to identify the variables that have the most significant influence on the quality of the Ordnance School. The sample used in this research was Probability Sampling, specifically random sampling, by distributing questionnaires to 226 respondents consisting of personnel/employees at the Ordnance School. The data was processed using SmartPLS Ver.3, which produced data analysis for the Validity and Reliability Tests, as well as Multiple Linear Regression Analysis. The t-test was used to determine whether the hypothesis was accepted or not. The results of the research show that the variable organizational culture has a significant partial effect on the quality of the Ordnance School, while management and personnel performance do not have a significant partial effect on the quality of the Ordnance School.